UMPSA celebrates 144 Excellent Staff and Quality and Innovation Day Award Recipients - Mimi Rabita, Abd Wahit (UMPSA, 2024)
GAMBANG, 24 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) celebrated a total of 144 recipients of the Outstanding Service Award and award recipients in conjunction with the UMPSA Quality and Innovation Day which took place at the Sports Complex Hall of the UMPSA Gambang Campus.